Dichotomy of Rhinoplasty Practice: From the Conference Floor to the Operating Room - Palma, Pietro; Khodaei, Iman (Facial Plastic Surgery, 2014)
Advancements in surgical techniques and improvements in clinical practice inevitably lag behind scientific progress and peer-led opinion. The rapid rise and fall in the popularity of rhinoplasty techniques makes scientific evidence-gathering and education a daunting task. Students of rhinoplasty face a long and steep learning curve, and need to acquire sound analytical tools to critically evaluate both literature contributions and operative reports shown in conferences. Such a complex learning process requires continuous self-examination, and must account for the increasingly sophisticated and intricate wishes of rhinoplasty patients whose desires do not always coincide with what surgeons have been taught and practiced. In contemporary practice, the developing rhinoplasty surgeon must be also familiar with the range of racial features, as the broad variety of nasal anatomies and beauty canons are truly staggering, and one formula does not fit all cases.The complex set of circumstances that lead to disharmony between scientific progress and clinical practice is addressed, and a utilitarian plan to remedy this awkward dichotomy is suggested.
Keywords: rhinoplasty education; evidence-based rhinoplasty; rhinoplasty techniques